2019
DOI: 10.1016/j.pnucene.2019.03.041
|View full text |Cite
|
Sign up to set email alerts
|

PARCS vs CORE SIM neutron noise simulations

Abstract: In a nuclear reactor, even operating at full power and steady-state conditions, fluctuations are detected in the recording of any process parameter. These fluctuations (also called noise) could be of various origins, such as, turbulence, mechanical vibrations, coolant boiling, etc. The monitoring and complete comprehension of those parameters should thus allow detecting, using existing instrumentation and without introducing any external perturbation to the system, possible anomalies before they have any inadv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Quite surprisingly, continuous-energy Monte Carlo simulations of the linearized noise equations independently performed by CEA and Kyoto University have also pointed out that in some circumstances the spectral peak at 2ω 0 might become (much) larger than the one at ω 0 1 . Neutron noise analysis is nowadays mostly based on state-of-the-art numerical codes, capable of taking into account arbitrary cross section variations in the time or frequency domain (Demazière, 2011;Yamamoto, 2013;Rouchon et al, 2017;Rohde et al, 2018;Olmo-Juan et al, 2019;Vidal-Ferrándiz et al, 2020;Chionis et al, 2020), as witnessed by the renewed interest stimulated by the CORTEX H2020 project (Demazière et al, 2018). For the case of frequency domain, newly developed transport (as opposed to diffusion) solvers (Rouchon, 2016;Yi et al, 2019) and Monte Carlo methods (Yamamoto, 2013;Rouchon et al, 2017) allow addressing realistic applications at the scale of fuel assemblies or full reactor cores with unprecedented accuracy (Demazière, 2011;Rouchon, 2016;Yamamoto, 2018;Mylonakis et al, 2019;Rouchon et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Quite surprisingly, continuous-energy Monte Carlo simulations of the linearized noise equations independently performed by CEA and Kyoto University have also pointed out that in some circumstances the spectral peak at 2ω 0 might become (much) larger than the one at ω 0 1 . Neutron noise analysis is nowadays mostly based on state-of-the-art numerical codes, capable of taking into account arbitrary cross section variations in the time or frequency domain (Demazière, 2011;Yamamoto, 2013;Rouchon et al, 2017;Rohde et al, 2018;Olmo-Juan et al, 2019;Vidal-Ferrándiz et al, 2020;Chionis et al, 2020), as witnessed by the renewed interest stimulated by the CORTEX H2020 project (Demazière et al, 2018). For the case of frequency domain, newly developed transport (as opposed to diffusion) solvers (Rouchon, 2016;Yi et al, 2019) and Monte Carlo methods (Yamamoto, 2013;Rouchon et al, 2017) allow addressing realistic applications at the scale of fuel assemblies or full reactor cores with unprecedented accuracy (Demazière, 2011;Rouchon, 2016;Yamamoto, 2018;Mylonakis et al, 2019;Rouchon et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, there has been a noticeable increase in neutron noise levels in certain German, Swiss, and Spanish reactors, of similar design (RSK/ESK 2013;Spanish Nuclear Safety Council 2011). This has led to a rise in the scientific interest and effort to understand its phenomenology as can be seen in different papers (Bermejo, Montalvo, and Ortego 2017;Olmo-Juan et al 2019;Seidl et al 2015;Tran, Pázsit, and Nylén 2015;Viebach et al 2018Viebach et al , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the influence of coherent lateral deflections for all FAs on the neutron flux was considered in (Seidl et al, 2015) and (Viebach et al, 2018). In the last years, some research aimed at comparing time domain and frequency domain calculations was reported (Chionis et al, 2017;Viebach et al, 2019;Olmo-Juan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%